Selected determinants of spirituality among nurses - Deluga, Alina; Dobrowolska, Beata; Jurek, Krzysztof; Nowicki, Grzegorz; Ślusarska, Barbara (Nursing in the 21st Century, 2021)
SELECTED DETERMINANTS OF SPIRITUALITY AMONG NURSESIntroduction. Spirituality has a multi-dimensional nature which influences the professional activities of nurses in a caring profession.Aim. Identifying selected determinants of spirituality among nurses and their relationship with socio-demographic factors.Material and methods. Research was conducted in 2018 on 144 nurses. All of the respondents were active in their profession. The research was made with diagnostic survey method using standardized research tools, including a Self-Description Questionnaire (SDQ), the Spiritual Transcendence Scale (STS), and the Brief Religious Coping (RCOPE) questionnaire, (BR).Results. It was established that age and professional seniority positively correlate with Religious Attitude (SDQ), p